Efektivitas Sistem Pengumpulan Pengelolaan Pendistribusian Dana Zakat Infak dan Shadaqah (Studi Kasus Baznas Kabupaten Lombok Timur) - Nur Hidayati (Penerbit Jurnal Indonesia, 2026)
The management of zakat institutions plays a central role in ensuring the effective collection, management, and distribution of Zakat, Infaq, and Sadaqah (ZIS), particularly in supporting poverty alleviation and strengthening community welfare. This study aims to analyze the effectiveness of the ZIS management system at the National Amil Zakat Agency (BAZNAS) of East Lombok Regency by examining the mechanisms of fundraising, fund management, and distribution, as well as identifying institutional challenges that affect performance outcomes. Employing a descriptive qualitative design supported by simple quantitative analysis, the research involved ten purposively selected informants consisting of BAZNAS administrators, UPZ officers, and mustahik beneficiaries. Data were collected through semi-structured interviews, direct observations, and document analysis, then processed through an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing with methodological triangulation to strengthen data validity. The findings reveal that BAZNAS East Lombok has implemented structured procedures aligned with Law No. 23 of 2011, supported by SIMBA-based reporting, village-level mustahik verification, and the Annual Work and Budget Plan (RAK) as an operational guide. Quantitative analysis using the Allocation to Collection Ratio (ACR) shows that the distribution performance from 2020 to 2023 consistently exceeded 90 percent, categorizing ZIS allocation as highly effective. However, several constraints were identified, including limited innovation in fundraising strategies, administrative inconsistencies, and irregular updating of beneficiary databases, which in turn influence the accuracy and sustainability of ZIS programs. Despite these challenges, ZIS distribution contributes significantly to fulfilling basic needs and supporting early economic empowerment among mustahik. This study concludes that the ZIS management system of BAZNAS East Lombok is effective but requires optimization, with recommendations emphasizing the development of digital-based fundraising, routine verification of mustahik data, and strengthened monitoring and evaluation mechanisms to enhance transparency, accountability, and long-term socio-economic impact.